Nutritional Components of Some Non-Conventional Leafy Vegetables Consumed in Cameroon - Aba Ejoh, Richard; Nkonga, Djuikwo Viviane; Inocent, Gouado; Moses, Mbofung Carl (Pakistan Journal of Nutrition, 2007)
The human population in tropical Africa depends largely upon a large number of edible leaves to meet up with shortages in minerals and vitamins. Data base on the nutritional value of these diverse plant foods is incomplete. Herein we report the nutritional components in four species of non conventional vegetables. Vernonia calvoana var. bitter, V. amygdalina, V. colorata and V. calvoana var. non bitter have high levels of proteins [between 18.16 and 24.12 g/100g Dry Weight (DW)]. Their amino acid composition compare favourably with that of WHO protein standard with the exception of the s-amino acids being the limiting amino acids. They also contain high levels of carotenoids (between 30 and 41.5 mg/100g DW), vitamin C between 137.5 and 197.5 mg/100g DW and dietary fibre (24.9-30.1 g/100g DW). Comparatively, the average nutritive value of the V. calvoana non bitter is superior to those the other species analyzed. High levels of some anti-nutritional factors like oxalic acids, polyphenols and saponins, were also found in all the species analyzed thereby rendering some of the important nutrients in the leaves less bio-available.